Total antioxidant activity of bovine milk: Phenotypic variation and predictive ability of mid-infrared spectroscopy. (February 2019) - Niero, Giovanni; Penasa, Mauro; Costa, Angela; Currò, Sarah; Visentin, Giulio; Cassandro, Martino; De Marchi, Massimo
Abstract: The phenotypic variation of milk total antioxidant activity (TAA) and the ability of mid-infrared spectroscopy to predict this novel trait was investigated. Total antioxidant activity was measured through the reference spectrophotometric method on 1249 individual milk samples of Holstein Friesian cows. Sources of variation of milk TAA were investigated using a mixed model, which included the fixed effects of days in milk, parity and calving season, and the random effects of herd-test-date and error. Mid-infrared spectroscopy prediction models were developed using partial least squares regression approach. The average level of milk TAA was 6.93 mmoL L −1 of Trolox equivalents; this exhibited a coefficient of variation of 15% and showed weak phenotypic correlations with milk quality traits. Values of TAA were lower in early lactation than in late lactation. Mid-infrared spectroscopy prediction models reached a coefficient of determination in external validation of 0.41, suggesting that they are not adequate for analytical purposes.